Evaluating the relationship between social media use frequency and entrepreneurial perceptions and attitudes among students. Issue 4 (April 2022) - Barrera-Verdugo, Gustavo; Villarroel-Villarroel, Antonio
Abstract: Despite studies published in the last decade linking entrepreneurship and the use of social media, to date, no study has analyzed in depth the relationship between the frequency of use among different social media sites and the intensity of entrepreneurial attitudes and perceptions. Due to the increasing use of social media as a teaching tool in higher education, this study seeks to address this knowledge gap. Consequently, the objective of this research is to analyze whether the frequency of social media use, among Twitter, Facebook, Instagram, WhatsApp and YouTube, is linked with perceptual discrepancies regarding entrepreneurial subjective norms, attitudes toward entrepreneurship and the intention to undertake, differentiating this relationship by gender and age group. A total of 246 business and engineering students from Chile were evaluated through online surveys, and Mann–Whitney and Spearman's correlation tests were performed. The findings highlight that higher exposure on these social media platforms is related to better entrepreneurial attitudes and perceptions, and this association differs according to students' gender and age group; in particular, Facebook shows more positive correlations in younger and male students, and WhatsApp and YouTube show more positive correlations in older and female students. This research extends the understanding of the relation between exposure to social media and variables with a considerable influence on undertaking entrepreneurship. Universities should integrate social media use as a teaching tool among students to aid in their entrepreneurial learning and strengthen new ventures. The main limitation of the study is that the sample includes business and engineering students in Chile. Future studies should ask students from different countries; likewise, it is important to use qualitative methodologies to determine why social media may affect entrepreneurial perceptions and attitudes. Abstract : Social media, Gender, Age, Subjective norms, Attitudes toward entrepreneurship, Entrepreneurial intention.